Peran Orang Tua terhadap Praktik Ibadah Salat Anak - Zulkaedah Zulkaedah (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
Lack of religious knowledge in children so that the performance of prayers does not meet the criteria. This study aims to: find out about parents' attention to children's prayer services, find out the obstacles to inhibiting parental attention to children's prayer services, and find out efforts to prevent obstacles to giving parents' attention to children's prayer services. This research method is qualitative research. Data collection in this research was obtained using observation methods, interviews, and documentation. The type of approach in this research used is field research approach. The results of this study show that parents' attention to children's prayer is still minimal so that there are still many children who have not prayed at the time of prayer. Obstacles that are encountered when giving attention to prayers to children are family factors, namely the limited religious knowledge of parents and the separation of parents, economic factors that are as both parents must make a living to meet their daily needs so that attention to their children is lost, and the interest in learning children who want to perform their prayers is very lacking. Efforts to give attention to children by carrying out routine activities, namely bringing children during congregational prayers in mosques and providing guidance to children in places of study and continued attention while at home.